Women’s Movements Against VAW and Feminicide: How Community-Based Feminisms Build Worlds Otherwise from the Periphery of Mexico City - María José Ventura Alfaro (Partecipazione e Conflitto, 2022)
In this article, I draw on feminist and new social movement literature to analyse contemporary Mexico's Women's Collective Action (WCA) through a framework of prefiguration. I challenge traditional epistemological analysis of social movement theory by engaging with Icaza's (2019) body-mind-spirit framework and Ahmed's (2004) cultural politics of emotions in my analysis of the cultural outcomes of the women's movements. By analysing emotions as cultural practices rather than psychological states, we can understand the intricate and at times contradictory reciprocal emotions at the inside of the women's movements. Similarly, analysing direct action through the body-mind-spirit framework, allows for a complex reading of direct action that transverses the body/mind cartesian dichotomy, instead understanding the body as the primary territory of defence in the healing, re-imagining and (re)building process of new relationships of doing and being. By engaging with an analysis of the contemporary Mexican feminist movement, I argue the WCA in Mexico is part of a new wave of hope movements which engage in a process of prefiguration through the construction of alternative, anti-patriarchal worlds in the present. Rather than one united front with a series of political goals, the only strategy this movement embodies is its desire to build (an)other worlds.